CoCa: a tool for analysing collaborative practices to improve design process management. (22nd March 2011) - Jared, Graham; Merlo, Christophe; Legardeur, Jérémy; Pol, Guillaume
This paper focuses on the coordination of engineering design from the collaboration point of view in order to help managers in controlling design processes. We focus on the organisation and process aspects to facilitate collaboration between designers and to foster the coordination of design projects by integrating the product, process and organisation points of view (PPO model). Indeed, the results of the collaborative design activities directly depend on relationships between design actors. Our aim is to allow project managers to enhance and control different types of collaborative processes in order to prescribe emerging collaboration between different experts. We propose then a method for storing and analysing collaborative processes in situ, in order that such processes can be formalised and re-used by project managers. This method is supported by a dedicated and implemented tool, called CoCa. A case study in an SME, designing and manufacturing innovative mechanical products, has been carried out to evaluate the possible feedback to design coordination, in particular by managing collaborative processes through PLM systems workflow technology.